Phenazine from Pseudomonas aeruginosa UPMP3 induced the host resistance in oil palm (Elaeis guineensis Jacq.)‑Ganoderma boninense pathosystem - Parvin, Waheeda; Govender, Nisha; Othman, Radziah; Jaafar, Hawa; Rahman, Mahbubur; Mui, Yun Wong (Springer Nature, 2020)
Pseudomonas aeruginosa developed its biocontrol agent property through the production of antifungal derivatives, with the phenazine among them. In this study, the applications of crude phenazine synthesized by Pseudomonas aeruginosa UPMP3 and hexaconazole were comparatively evaluated for their effectiveness to suppress basal stem rot infection in artificially G. boninense-challenged oil palm seedlings. A glasshouse experiment under the randomized completely block design was set with the following treatments: non-inoculated seedlings, G. boninense inoculated seedlings, G. boninense inoculated seedlings with 1 mg/ml phenazine application, G. boninense inoculated seedlings with 2 mg/ml phenazine application and G. boninense inoculated seedlings with 0.048 mg/ml hexaconazole application. Seedlings were screened for disease parameters and plant vigour traits (plant height, plant fresh weight, root fresh, and dry weight, stem diameter, and total chlorophyll) at 1-to-4 month post-inoculation (mpi). The application of 2 mg/ml phenazine significantly reduced disease severity (DS) at 44% in comparison to fungicide application (DS = 67%). Plant vigour improved from 1 to 4 mpi and the rate of disease reduction in seedlings with phenazine application (2 mg/ml) was twofold greater than hexaconazole. At 4, 6 and 8 wpi, an up-regulation of chitinase and β-1,3 glucanase genes in seedlings treated with phenazine suggests the involvement of induced resistance in G. boninense-oil palm pathosystem.